The diaconal and liberation role of the church in the fight against HIV / AIDS in Botswana - Ruele, Moji (Botswana Notes & Records, 2003)
In my view the church is more challenged than ever before to develop a theology, which is life, based. The development of such a theology would allow the church not only to preach and minister the Word of God to the suffering effectively, but also provide practical service to those who are directly infected and affected by HIV/AIDS. The church is also challenged to act decisively, because beside, the fact that HIV/AIDS is a matter of life and death, it has raised questions, which are always anguishing and in most cases difficult to answer.
Free